Pachymic acid induces apoptosis via activating ROS-dependent JNK and ER stress pathways in lung cancer cells - Ma, Jun (Cancer Cell Int, 2015)
BACKGROUND: Pachymic acid (PA), a lanostane-type triterpenoid from Poria cocos, has been reported to possess anti-emetic, anti-inflammatory, and anti-cancer properties. Nonetheless, the anti-tumor effect of PA in lung cancer cells remains unclear. Herein, we report the chemotherapeutic effects and underlying mechanisms of PA against human lung cancer. METHODS: The anti-proliferative ability of PA on lung cancer cells was assessed by MTT, colony formation and EdU proliferation assays. Flow cytometric analysis was used to detect cell cycle changes. Apoptosis was determined by annexin V/PI double-staining and the DNA ladder formation assays. The expressions of the apoptosis-related proteins were analysed by western blot. The in vivo efficacy of PA was measured using a NCI-H23 xenograft model in nude mice. RESULTS: PA exhibited anti-tumor effects in vitro accompanied by induction of G2/M phase arrest and apoptosis in NCI-H23 and NCI-H460 lung cancer cells. Mechanistically, our data showed that PA induced reactive oxygen species (ROS) production, resulting in the activation of both c-Jun N-terminal kinase (JNK) and endoplasmic reticulum (ER) stress apoptotic pathways in lung cancer cells. Moreover, blockage of ROS production reversed PA-induced JNK and ER stress activation. Finally, PA inhibited the growth of NCI-H23 xenograft tumors without causing any host toxicity, and inhibited cell proliferation and induction of apoptosis of tumor cells in tumor xenograft tissues. CONCLUSIONS: In summary, our study demonstrates that PA induces apoptosis through activation of the JNK and ER stress pathways in human lung cancer cells. Our findings provide a rationale for the potential application of PA in lung cancer therapy.